Legal Analysis Regarding Reviews Even If A Court’s Decision Has Permanent Legal Force - Timomor, Adensi; Pangalila, Theodorus (Technium Social Sciences Journal, 2023)
Even though a law has been made in detail regarding the review procedure, it does not mean that it has been able to anticipate everything. There is a possibility of errors or mistakes and the inability of written law to adjust the development of human civilization according to its era. When we take advantage of knowledge and technology it is possible to cause harm to the accused or someone this can happen. This problem raises questions academically regarding judicial review which can be carried out more than once even though the court’s decision already has permanent legal force. Therefore, the aim of this research is to do it more than once, even though the court’s decision already has permanent legal force. While the method used in this research is normative legal research or library research. This type of research examines laws that are conceptualized as norms or rules that apply. The results of this study indicate that the judicial review (PK) as stipulated in Law Number 8 of 1981 concerning the Criminal Procedure Code currently aims to realize justice for justice seekers. In addition, the judicial review aims to guarantee humane treatment of victims or defendants or convicts in finding justice.